Cellular uptake and internalization of hyaluronan-based doxorubicin and cisplatin conjugates. (August 2014) - Cai, Shuang; Alhowyan, Adel Ali B.; Yang, Qiuhong; Forrest, W. C. Melanie; Shnayder, Yelizaveta; Forrest, M. Laird
Abstract Background: Hyaluronan (HA) is a ligand for the CD44 receptor which is crucial to cancer cell proliferation and metastasis. High levels of CD44 expression in many cancers have encouraged the development of HA-based carriers for anti-cancer therapeutics. Purpose: The objective of this study was to determine whether HA conjugation of anticancer drugs impacts CD44-specific HA-drug uptake and disposition by human head and neck cancer cells. Methods: The internalization and cellular disposition of hyaluronan-doxorubicin (HA-DOX), hyaluronan-cisplatin (HA-Pt), and hyaluronan-cyanine7 (HA-Cy7) conjugates were investigated by inhibiting endocytosis pathways, and by inhibiting the CD44-mediated internalization pathways that are known to mediate hyaluronan uptake in vitro. Results: Cellular internalization of HA was regulated by CD44 receptors. In mouse xenografts, HA conjugation significantly enhanced tumor cell uptake compared to unconjugated drugs. Discussion: The results suggested that the main mechanism of HA-based conjugate uptake may be active transport via CD44 in conjunction with a clathrin-dependent endocytic pathway. Other HA receptors, hyaluronan-mediated motility receptor (RHAMM) and lymphatic vessel endothelial hyaluronan receptor (LYVE-1), did not play a significant role in conjugate uptake. Conclusions: HA conjugation significantly increased CD44-mediated drug uptake and extended the residence time of drugs in tumor cells.